Towards a framework for ‘significant’ learning in architectural education - Nikhil S. Kohale; Pradeep G. Kini; Ciraj Ali Mohammed (Cogent Education)
Architectural education often promises to question its intentions by aligning its methodologies to navigate through its dynamic environment and correspond to the contemporary requirements. The quality of a learner’s progression can be enhanced by designing meaningful learning experiences. By rethinking the nature of assessment and its relationship with learning, a deeper understanding and broader interpretations of learning can be explored. The prime objective of this study is to gain perspectives on learning which can enable a holistic learning and assessment of the learner’s progression that is aligned to meet its inherent criteria. This qualitative study explores a constructivist research design. It combines a literature study about aspects of learning in architecture with a case study approach in the realms of academics and practice by interacting with experts identified through purposive sampling. Recognizing the pivotal role of the affective domain in a designer’s learning process, the paper uses analogical reasoning in suggesting the adoption of Fink’s Taxonomy of Significant Learning as a suitable learning framework. Through those interpretations the study proposes a broad conceptual framework for learning as a contribution to the field of design creativity and innovation.